Nilai Sense of Community pada Kesejahteraan Psikologis dalam Menghuni (Housing Well-being): Studi Meta-analisis - Intan Rahmawati (Psikohumaniora: Jurnal Penelitian Psikologi, 2017)
Abstract: Well-being appreciates as a holistic unity of one's potential and a state where individuals can receive strengths and weaknesses, have a purpose in life, develop positive relationships that lead to personal growth wherever individuals are, especially in their neighborhoods. The shelter that spawned a housing well-being that looked at the potential benefits optimally could be likened to where he/she lived. Housing well-being requires reflective and formative as a benchmark to assess the welfare of individuals in their dwellings. Formative indicators point to the evaluation of the satisfaction of residential features, while reflective indicators look at the gap between expectations and existing in the neighborhood, one of which is in the neighboring neighborhoods that are part of the residential community. Sense of community is an early stage in the individual to see the community. Based on the map of existing research results in terms of residential satisfaction. The study used this meta-analysis strategy to examine the results of previous research on the consistency between the sense of community in shaping housing welfare. This meta-analysis study resulted that a sense of community contributing to housing welfare.Abstrak: Kesejahteraan psikologis dijelaskan sebagai suatu pencapaian yang holistik dari potensi psikologis seseorang dan suatu keadaan ketika individu dapat menerima kekuatan maupun kelemahan, memiliki tujuan hidup, mengembangkan relasi positif yang bermuara pada pertumbuhan pribadi dimanapun individu berada, terlebih dalam lingkungan tinggalnya. Konsep kesejahteraan psikologis inipun berkembang dalam lingkup hunian yang mencetuskan perspektif kesejahteraan psikologis dalam menghuni (housing well-being) yang memandang pada pencapaian potensi secara optimal beserta fungsi psikologis positif seseorang terhadap tempat tinggalnya. Pada indikatornya, housing well-being mensyaratkan reflektif dan formatif sebagai tolak ukur untuk menilai kesejahteraan psikologis individu pada huniannya. Indikator formatif menunjuk pada evaluasi kepuasan menyeluruh fitur hunian, sementara indikator reflektif melihat pada senjang antara harapan dan kenyataan yang ada di lingkungan tinggal, salah satunya adalah kepuasan dalam bertetangga yang merupakan bagian dari komunitas tinggal. Sense of community merupakan tahap awal dalam diri  individu  untuk  melihat  komunitasnya.  Berdasarkan peta penelitian  diperoleh  hasil bahwa terdapat peran sense of community dalam housing well-being. Penelitian yang menggunakan strategi meta-analisa ini bertujuan untuk mengkaji hasil-hasil penelitian yang telah dilakukan peneliti sebelumnya tentang kekonsistenan antara sense of community dalam membentuk housing well-being. Studi meta-analisis ini menghasilkan bahwa sense of community memberikan kontribusi terhadap housing well-being.